The Effects Of Orography On Wind, Cloud, And Rainfall Patterns During Typhoon Ketsana (2009) - Tan , Fuyi (2012)

(untitled)
Understanding the orographic effect is crucial for both disaster prevention and weather prediction for events such as tropical cyclones (TCs). Because of the complexity of orographic effects, due to the presence of mountains, the influence of orography on TCs remains unclear and is an active area of scientific research. The objective of this study is to investigate the effects of orography on the rainfall, wind, and cloud systems of the TCs in Malaysia, as this type of study has never been performed in Malaysia.